Pengembangan alat ukur kapasitas vital paru-paru dan frekuensi pernapasan manusia berbasis sensor serat optik - Mega Roza Lia; Harmadi Harmadi; Afdhal Muttaqin (Universitas Andalas, 2023)
The development of measuring instruments for vital lung capacity and human respiratory rate based on the fiber-optic sensor has a system consisting of a laser diode as a light source, optical fiber as a waveguide, and OPT101 as a photodetector. This research consists of three stages: hardware design, software design, and data analysis. Each component used is tested and then tested on the entire system to determine each component's performance when used together. In the software system, the analog signal in the form of voltage from OPT101 is converted into an ADC value by an analog-to-digital converter. Based on the ADC value obtained, the threshold value is determined as the threshold for reading the respiratory rate. The number of ADC values ​​during the measurement of vital lung capacity is then converted to volume. Testing of measuring instruments is carried out by comparing the results of instruments developed with a standard medical measuring device. The results of the tests and analyses that have been carried out have obtained an accuracy value of 92.62% for the measurement of vital lung capacity, 95.14% for the measurement of respiratory rate, and 92.62% for the measurement of the respiratory rate of variations in activity.